IMPLEMENTING THE MERDEKA CURRICULUM IN BORDER AREAS: CHALLENGES, ADAPTATION AND THE NEED FOR POLICY INTERVATION - Fernandez, Aloysius Joakim; Lakapu, Meryani; Kaluge, Agapitus Hendrikus (JME (Journal of Mathematics Education), 2025)
The implementation of the Merdeka Curriculum in border areas faces complex challenges, particularly in schools such as SMP Negeri Silawan and SMP Negeri SATAP Suspini. This study aims to describe the dynamics of teachers’ adaptation to Merdeka Curriculum within the context of infrastructural limitation, socio-econimic contiditions and local cultural values. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations and document analysis. The results reval that despite  strong commitment from schools and teachers, key obstacles such as limited access to training, inadequate facilities and low digital literacy continue to hinder effevtive implementation. However, adaptive strategies such as teacher collaboration, modification of teaching materials and the integration of of local cultural values into learning processes show potential to enhance curriculum relevance. These results highlight the need to strengthen teacher capacity about learning methods, improve infrastructure and provide greater flexibility in curriculum application to suit local contexts in border areas.